2008
DOI: 10.1007/s11695-008-9764-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Laparoscopic Roux-en-Y Gastric Bypass on Metabolic Syndrome, Inflammation, and Insulin Resistance in Super Versus Morbidly Obese Women

Abstract: One year after surgery, LRYGBP was equally effective at reversing metabolic syndrome, inflammation, and insulin resistance in morbidly obese and super-obese women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 30 publications
3
21
0
2
Order By: Relevance
“…Most publications have concentrated on the gastric bypass [11][12][13][14][15]. Batsis et al [24] compared gastric bypass with medical management of the metabolic syndrome and found a significant difference at 12 months in favor of surgery (87% to 29% at 12 months), while medical management showed much less efficacy (85% to 75% at 12 months).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most publications have concentrated on the gastric bypass [11][12][13][14][15]. Batsis et al [24] compared gastric bypass with medical management of the metabolic syndrome and found a significant difference at 12 months in favor of surgery (87% to 29% at 12 months), while medical management showed much less efficacy (85% to 75% at 12 months).…”
Section: Discussionmentioning
confidence: 99%
“…Studies evaluating the impact of sleeve gastrectomy on the metabolic syndrome are rare and contradictory. Iannelli et al [14], comparing gastric bypass (n = 5) and sleeve gastrectomy (n = 6), found a statistically significant difference in the postoperative prevalence of the metabolic syndrome at 12 months follow-up in favor of the gastric bypass (P < 0.005). The small numbers in each group, however, constitute a serious bias in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence suggests that bariatric surgery, especially Roux-en-Y gastric bypass (RYGB), represents the most effective intervention in obesity treatment, resulting not only in major and sustained weight loss but also in an amelioration of insulin sensitivity and lipid profile [2][3][4][5][6]. The pathophysiological mechanisms linking obesity and insulin resistance, however, have not been completely elucidated to date.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been reported that resolution of MetS is similar in obese and superobese patients at first year following LRYGBP [23], it has not been reported what happens to MetS in long term when superobese patients gain weight (LRYGBP can fail in 35% of superobese patients [24]). Besides, it has been demonstrated that weight gain can develop or worsen diabetes over the years [25].…”
Section: Discussionmentioning
confidence: 98%